2022
DOI: 10.1111/acel.13545
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic progenitor cell liabilities and alarmins S100A8/A9‐related inflammaging associate with frailty and predict poor cardiovascular outcomes in older adults

Abstract: Frailty affects the physical, cognitive, and social domains exposing older adults to an increased risk of cardiovascular disease and death. The mechanisms linking frailty and cardiovascular outcomes are mostly unknown. Here, we studied the association of abundance (flow cytometry) and gene expression profile (RNAseq) of stem/progenitor cells (HSPCs) and molecular markers of inflammaging (ELISA) with the cardiorespiratory phenotype and prospective adverse events of individuals classified according to levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Increasing evidence demonstrated that EGR1 [88], RNASE2 [89], CD163 [90] and S100A8 [91], and its protein product has a function in respiratory viral infections. EGR1 [92], ATF3 [93], XIST (X inactive specific transcript) [94], S100A12 [95] and S100A8 [96] were identified as a candidate genes of heart problems. EGR1 [97], ATF3 [63] and XIST (X inactive specific transcript) [98] are involved in the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrated that EGR1 [88], RNASE2 [89], CD163 [90] and S100A8 [91], and its protein product has a function in respiratory viral infections. EGR1 [92], ATF3 [93], XIST (X inactive specific transcript) [94], S100A12 [95] and S100A8 [96] were identified as a candidate genes of heart problems. EGR1 [97], ATF3 [63] and XIST (X inactive specific transcript) [98] are involved in the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was isolated starting from 2 × 10 6 cells using the RNeasy Mini Kit (QIAGEN, Hilden, Germany) and following manufacturer’s instructions, while RNA-seq libraries were prepared and sequenced in triplicate for each experimental condition, as already described [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…These mediators activate many signaling pathways influencing immune function, leading to a gradual deterioration of the immune system, known as immunosenescence 181 . Accumulating evidence suggests that both inflammaging and immunosenescence are responsible for most aging-related diseases, including but not limited to disorders pertaining to the cardiovascular 182 , neurological 183 , respiratory 184 and digestive systems 143 .…”
Section: Promising Therapeutics Targeting Agingmentioning
confidence: 99%